Business Development Strategies of USK Tour and Travel: A SWOT Analysis from an Islamic Economic Perspective - Zaidan Shadiq Ridhwana; Teuku Meldi Kesuma; Khairil Umuri; Radhia Humaira (PROCEEDING INTERNATIONAL BUSINESS AND ECONOMICS CONFERENCE (IBEC), 2025)
USK Tour and Travel is a business unit under Universitas Syiah Kuala operating in the travel and tourism services sector. This study aims to analyze the business development strategy of USK Tour and Travel using the SWOT analysis approach and examine its alignment with Islamic economic values. A qualitative descriptive method was used, with data gathered through interviews, observations, and documentation. Based on the analysis, USK Tour and Travel is positioned in Quadrant I (S–O Strategy), indicating strong internal capabilities and favorable external opportunities. The recommended strategies include leveraging institutional support and academic networks to optimize growth in the halal and educational tourism sector, enhancing digital marketing, improving human resource capacity, and establishing strategic partnerships. From an Islamic economic perspective, core values such as shiddiq (honesty), amanah (trustworthiness), fathanah (intelligence), tabligh (communication), and istiqamah (consistency) are being implemented but require further integration into daily business practices to achieve both profitability and spiritual value. This research is expected to serve as a reference for businesses aiming to develop within an Islamic ethical framework in the tourism industry.